2015
DOI: 10.1007/s10508-015-0503-7
|View full text |Cite
|
Sign up to set email alerts
|

Stigma-Related Stress and Its Correlates Among Men with Pedophilic Sexual Interests

Abstract: Despite decades of research on the adverse consequences of stereotyping and discrimination for many stigmatized groups, little is known about how people with pedophilia perceive and react to stigma. In this article, we present a framework that outlines how stigma-related stress might negatively affect emotional and social areas of functioning, cognitive distortions, and the motivation to pursue therapy, all of which may contribute to an increased risk of sexual offending. We tested our hypotheses in an online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(159 citation statements)
references
References 62 publications
10
139
1
9
Order By: Relevance
“…In a sample of non-offending pedophilic individuals, high levels of perceived social distance and fear of discovery were reported [21]. When this sample of non-offending pedophiles was compared with the normative samples for the self-reported measures used in the research, pedophilic individuals were found to have higher levels of psychopathology and social isolation and lower problem-focused approaches to coping with stress (e.g., not reacting with strong emotion or using wishful thinking to cope with stress).…”
Section: Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…In a sample of non-offending pedophilic individuals, high levels of perceived social distance and fear of discovery were reported [21]. When this sample of non-offending pedophiles was compared with the normative samples for the self-reported measures used in the research, pedophilic individuals were found to have higher levels of psychopathology and social isolation and lower problem-focused approaches to coping with stress (e.g., not reacting with strong emotion or using wishful thinking to cope with stress).…”
Section: Stigmamentioning
confidence: 99%
“…Nonoffending pedophiles have similar levels of working memory and selective attention for sexual cues as non-pedophilic men [20]. In addition, compared with incarcerated pedophiles, non-offending pedophiles have also been found to display less supportive attitudes toward sex with children and higher levels of self-efficacy for controlling sexual urges [21]. A further comparative study found that a sample of pedophilic men (55 % non-offending) had stronger automatic and implicit associations between children and sex than non-pedophilic men, providing support that implicit cognition plays a role in sexual interest in children [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, self-stigmatization among pedophiles has been found to contribute to a fear of discovery, as well as reductions in cognitive and emotional functioning (Jahnke, Schmidt, Geradt, & Hoyer, 2015). Given that these are potential risk factors for the commission of sexual offending (e.g., Gillespie, Mitchell, Fisher, & Beech, 2012), it can be argued that reducing NARRATIVES AND PEDOPHILIA JUDGMENTS 5 stigmatization of non-offending pedophiles could contribute to reductions in sexual offending behavior.…”
Section: Stigmatization and Pedophiliamentioning
confidence: 99%
“…Ricciardelli & Moir, 2013). Research suggests that expectations of stigmatisation can result in significant negative consequences, including recidivism (Braithwaite, 1989;LeBel et al, 2008) and sexual violence (Jahnke et al, 2015). Such fears were clear among the present research sample who described harassment and hatred from others aimed at both themselves and their families:…”
Section: Discussionmentioning
confidence: 65%